'Theological Wars': 'Socinians' v. 'Antinomians' in Restoration England. Issue 2 (3rd March 2016) - HAIGH, CHRISTOPHER
Abstract : This article examines changes in content and tone in some polemical exchanges between Anglican conformists and Nonconformists in the reign of Charlesii . In response to the Dissenters' pleas for comprehension and/or toleration because of shared Protestant beliefs, some conformists accused them of holding an antinomian doctrine of justification that undermined morality and political order – and Dissenters retorted with accusations of Socinianism. The disputes were complicated by divisions over justification within rather than between Anglican and Nonconformist groups, and by the late 1670s the perceived threats from papists brought renewed emphasis on common ground